371. MAPPING OF LYMPH NODE METASTASIS IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA AT ESOPHAGOGASTRIC JUNCTION: A RETROSPECTIVE SURGICAL STUDY COHORT. (24th September 2022) - Jiang, Chao; Liu, Zhichao; Li, Chunguang; Sun, Yifeng; Guo, Xufeng; Hua, Rong; He, Yi; Yang, Yang; Zhang, Jie; Wei, Jinzhi; Li, Zhigang
Abstract: The aim of this study was to determine the optional extent of lymph node dissection of the squamous cell carcinoma (SCC) at the esophagogastric junction (EGJ) based on the incidence of metastasis in a retrospective single-center study. Patients with SCC involving and within 5 cm of the esophagogastric junction (EGJ) who underwent McKeown esophagectomy without preoperative treatment were reviewed in a prospectively maintained database at a single institution from 2015 to 2021. Lymph nodes stations was based on the definitions from the Japan Esophageal Society, and lymph nodes were further classified according to the metastatic incidence rate, as follows: Category-1 (strongly recommended for dissection), rate of more than 10%; Category-2 (weakly recommended for dissection), rate of from 5% to 10%; and Category-3 (not recommended for dissection), rate of less than 5%. Sixty-one patients were identified. T stage was pT1 (n = 9), pT2 (n = 11), pT3 (n = 40), and pT4 (n = 1). For all patients, category-1 nodes were predominantly abdominal stations (1, 2, 3, 7) and lower mediastinal stations (110); category-2 nodes were upper-middle mediastinal stations (105, 106recR, 107, 108); station 106recL was category-3 with a metastasis rate of 4.92%. More nodal metastases were observed in cases with upper-margin exceeding EGJ >3 cm, and station 106recL was upgraded to category-2. For pT1 SCC, category-1 was focused on station 111, with no nodal metastasis in upper-middle mediastinal. For pT2 and pT3 SCC, cervical, thoracic, and abdominal lymph node metastases were found. Radical total mediastinal lymph node dissection is as important as abdominal dissection for SCC at EGJ, but lymph node dissection around the left recurrent laryngeal nerve appears to be exempt in T1 patients.